Updated ethnobotanical notes, phytochemistry and phytopharmacology of plants belonging to the genus Morus (Family: Moraceae) - Sonam Yadav; Nisha Nair; Avadh Biharee; Vivek Morris Prathap; Jaseela Majeed (Elsevier, 2022)
Background: : Mulberry (Genus: Morus, Family: Moraceae) is a flowering plant utilized in Traditional Chinese Medicine (TCM) and Ayurveda for its ethnobotanical uses in fever, liver protection, diuretics, management of appropriate blood pressure, improving eyesight, and management of cardiovascular disease. Being a plant of multiple ethnobotanical prospects, it is used to prevent kidney diseases, hair problems, weakness, fatigue, constipation, blood disorders, anemia, and premature greying of hair, among few other ailments. This review aims to systematically organize information on the ethnobotanical uses, phytochemical constituents, phytopharmacological actions, and toxicity of the Morus genus as the information shall serve towards future research in drug discovery and help in unearthing molecular basis of pharmacological activity of Mulberry. Method: : Many relevant information sources, such as Elsevier, Science Direct, PubMed, ACS Publications, SciFinder, Wiley, and Google Scholar, Chinese Pharmacopoeia 2015, Chinese and Indian herbal classic texts, and Ph.D. dissertation, were used to gather relevant publications till February 2021 on the Morus genus. Results: : Many phytochemicals that are isolated from Morus genus such as Mulberrin, Morin, Deoxynojirimycin (DNJ), Epicatechin, Gallic acid, Vanillic acid, Oxyresveratrol, Quercetin, Flavone A, B and C, are proven to be pharmacologically important and have comprehensive biological actions such as anti-inflammatory, anticancer, antibacterial, anti-obesity, antidopaminergic, antioxidant activity, as well as skin whitening properties making the plants of Morus genus therapeutically important. Conclusions: : Plants of Morus genus are valuable and are popular in ancient herbal medicine with the extensive pharmacological potential to cure various ailments. While phytochemicals from plants of Morus genus have already been extensively analysed, there may still be unknown compounds that play a role in the plant's biological function which needs to be elucidated. There are significant gaps in our understanding of biological processes involved in activities of these phytochemicals that need more investigation.